2013
DOI: 10.1111/jtm.12047
|View full text |Cite
|
Sign up to set email alerts
|

Major West Indies MRSA Clones in Human Beings: Do They Travel With Their Hosts?

Abstract: The distribution of the major MRSA clones in the French (Guadeloupe and Martinique) and non-French West Indies (Jamaica, Trinidad, and Tobago) is different, and the clones most closely resemble those found in the home countries of the travelers who visit the islands most frequently. The distribution might be affected by tourist migration, which is specific to each island.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The distribution of the major AMR organisms such as Methicillin-resistant Staphylococcus aureus (MRSA) clones in the French (Guadeloupe and Martinique) and non-French territories (Jamaica and Trinidad and Tobago) were shown to be different. The clones most closely resembled those found in the home countries of the travelers who visit the islands [28]. This implies the potential that the distribution of AMR is affected by tourist migration and further reveals the importance of this study.…”
Section: Discussionmentioning
confidence: 52%
“…The distribution of the major AMR organisms such as Methicillin-resistant Staphylococcus aureus (MRSA) clones in the French (Guadeloupe and Martinique) and non-French territories (Jamaica and Trinidad and Tobago) were shown to be different. The clones most closely resembled those found in the home countries of the travelers who visit the islands [28]. This implies the potential that the distribution of AMR is affected by tourist migration and further reveals the importance of this study.…”
Section: Discussionmentioning
confidence: 52%
“…In our study, we found a significant association between MSSA infection and immigrant status (Table 3). The impact of travel and migration on MSSA and MRSA geographic variation will undoubtedly become more evident as surveillance networks capture these differences, such as the studies performed in the Caribbean by the Etienne-Tristan group from Lyon, France [34,35] and the Uhlemann-Lowy team from New York, US [34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…The global rising problem of antibiotic resistance has also been linked to international travel. The worldwide spread of certain antibiotic resistant Staphylococcus aureus has been linked to tourism, which shows the potential impact on international health ( 50 , 51 ). Faecal colonization with ESBL-producing Enterobacteriaceae has also been linked to international travellers in several studies ( 52 54 ).…”
Section: Modern Cities a Catalyst For Rapid Spread Of Infectious Disementioning
confidence: 99%